GuitarPD: A Randomized Pilot Study on the Impact of Nontraditional Guitar Instruction on Functional Movement and Well-Being in Parkinson’s Disease - Serap Bastepe-Gray; Lavinia Wainwright; Diane C. Lanham; Gabriela Gomez; Jieung S Kim; Zane Forshee; Bonnie Kaas; Arita McCoy; Colin McGregor; Emile Moukheiber; Suraj Rajan; Gerson Suarez-Cedeno; et al. (Parkinson's Disease)
Playing musical instruments may have positive effects on motor, emotional, and cognitive deficits in patients with Parkinson’s disease (PD). This pilot study examined the feasibility of a six-week nontraditional guitar instruction program for individuals with PD. Twenty-six participants with idiopathic PD (Age: 67.22 ± 8.07; 17 males) were randomly assigned to two groups (intervention first or 6 weeks of usual care control exposure) with stepwise exposure to the guitar intervention condition with cross-over at six weeks. Outcomes were assessed at baseline, 6, 12, and 18 weeks. Twenty-four participants completed the study. Combined analysis of the groups showed significant BDI-II improvement immediately after intervention completion (3.04 points, 95% CI [−5.2, −0.9], p=0.04). PDQ-39 total quality of life scores improved from baseline to immediately postintervention 5.19 points (95% CI [−9.4, −1.0]) at trend significance (corrected p=0.07). For Group 1 (exposed to the intervention first), MDS-UPDRS total scores improved by a mean of 8.04 points (95% CI [−12.4, −3.7], p=0.004) and remained improved at 12 weeks by 10.37 points (95% CI [−14.7, −6.0], p<0.001). This group also had significant improvements in mood and depression at weeks 6 and 12, remaining significant at week 18 (BDI-II: 3.75, 95% CI [−5.8, −1.7], p=0.004; NeuroQoL-depression: 10.6, 95% CI [−4.9. −1.4], p=0.004), and in anxiety at week 6 and week 18 (NeuroQoL; 4.42, 95% CI [−6.8, −2.1], p=0.004; 3.58, 95% CI [−5.9, −1.2], p=0.02, respectively). We found clinically and statistically significant improvements in mood/anxiety after 6 weeks of group guitar classes in individuals with PD. Group guitar classes can be a feasible intervention in PD and may improve mood, anxiety, and quality of life.